Tests on the Vacuum-Aided Casting Technique for Concrete in Tubes of Concrete-Filled Steel Tube Arch Bridges and Its Engineering Applications. Issue 1 (2nd January 2018) - Yu, Han
Abstract: To address the interfacial concrete separation problem of concrete-filled steel tube arch bridges, 250 m long steel tube models were designed and fabricated for comparative tests, where the vacuum-aided grouting technique and the normal pressure grouting procedure were employed, respectively, to cast the concrete in tubes. The ultrasonic detection method and the cutting inspection method were applied to the experimental concrete-filled tubes to verify the effectiveness of the vacuum-aided grouting technique, of which the working mechanism was also clarified. In turn, the defects and the corresponding measures for the improvement of the original vacuum-aided grouting technique were discussed. Finally, the improved technique was applied in the construction of real bridge engineering to actually realize full-process, vacuum-aided grouting. The developed technique greatly reduces the interfacial concrete separation areas as well as the long-term separation distances and effectively ensures the compactness of the cast concrete in the steel tubes. This technique has been patented and generalized to the construction of three super-span arch bridges.